Depletion of carbohydrate reserves limits nitrate uptake during early regrowth in Lolium perenne L - Guo, Qianqian; Turnbull, Matthew Hamish; Song, Jiancheng; Roche, Jessica; Novak, Ondrej; Späth, Jana; Jameson, Paula Elizabeth; Love, Jonathan (Journal of experimental botany, 2017)
The mechanisms linking C/N balance to N uptake and assimilation are central to plant responses to changing soil nutrient levels. Defoliation and subsequent regrowth of grasses both impact C partitioning, thereby creating a significant point of interaction with soil N availability. Using defoliation as an experimental treatment, we investigated the dynamic relationships between plant carbohydrate status and NO3--responsive uptake systems, transporter gene expression, and nitrate assimilation in Lolium perenne L. High- and low-affinity NO3- uptake was reduced in an N-dependent manner in response to a rapid and large shift in carbohydrate remobilization triggered by defoliation. This reduction in NO3- uptake was rescued by an exogenous glucose supplement, confirming the carbohydrate dependence of NO3- uptake. The regulation of NO3- uptake in response to the perturbation of the plant C/N ratio was associated with changes in expression of putative high- and low-affinity NO3- transporters. Furthermore, NO3- assimilation appears to be regulated by the C-N status of the plant, implying a mechanism that signals the availability of C metabolites for NO3- uptake and assimilation at the whole-plant level. We also show that cytokinins may be involved in the regulation of N acquisition and assimilation in response to the changing plant C/N ratio.
Keywords: Plant Leaves; nitrogen use efficiency (NUE); perennial ryegrass.; Carbohydrate; Nitrogen; Lolium perenne; dusík; cytokinin; Carbohydrate Metabolism; dusičnany; regulace genové exprese u rostlin; metabolismus sacharidů; listy rostlin; Gene Expression Regulation, Plant; Lolium; rostlinné proteiny; nitrate transporter (NRT); Nitrates; Plant Proteins; jílek; fructan; carbon; nitrate uptake; nitrogen